2009
DOI: 10.1074/jbc.m808632200
|View full text |Cite
|
Sign up to set email alerts
|

Plant Vacuolar ATP-binding Cassette Transporters That Translocate Folates and Antifolates in Vitro and Contribute to Antifolate Tolerance in Vivo

Abstract: The vacuoles of pea (Pisum sativum) leaves and red beet (Beta vulgaris) storage root are major sites for the intracellular compartmentation of folates. In the light of these findings and preliminary experiments indicating that some plant multidrug resistance-associated protein (MRP) subfamily ATP-binding cassette transporters are able to transport compounds of this type, the Arabidopsis thaliana vacuolar MRP, AtMRP1 (AtABCC1), and its functional equivalent(s) in vacuolar membrane vesicles purified from red bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…S7). Under standard growth conditions, AtABCC1 and AtABCC2 single and double knockout mutants exhibit no mutant phenotypes (Raichaudhuri et al, 2009;Park et al, 2012). We also did not observe growth phenotypes of these mutant seedlings subjected to drought and osmotic stress.…”
Section: Atabcc1 and Atabcc2 Transcript Levels And Knockout Phenotypementioning
confidence: 48%
See 1 more Smart Citation
“…S7). Under standard growth conditions, AtABCC1 and AtABCC2 single and double knockout mutants exhibit no mutant phenotypes (Raichaudhuri et al, 2009;Park et al, 2012). We also did not observe growth phenotypes of these mutant seedlings subjected to drought and osmotic stress.…”
Section: Atabcc1 and Atabcc2 Transcript Levels And Knockout Phenotypementioning
confidence: 48%
“…The Arabidopsis AtABCC1 and especially AtABCC2 mediate the transport of structurally diverse metabolites, such as phytochelatins, folates, and conjugates of chlorophyll catabolite and xenobiotics (Liu et al, 2001;Frelet-Barrand et al, 2008;Raichaudhuri et al, 2009;Song et al, 2010). We expressed AtABCC2 in yeast and observed a distinct MgATP-dependent ABA-GE transport activity of isolated membrane vesicles (Fig.…”
Section: Atabcc1 and Atabcc2 Transcript Levels And Knockout Phenotypementioning
confidence: 99%
“…These studies indicate that a steady pool of folate cofactors is essential to sustain actively dividing cells in the root tip. Indeed, pharmacological induction of folate deficiency in plants caused a reduction in cell division in Arabidopsis suspension cells and an inhibition of seedling growth (Loizeau et al, 2007(Loizeau et al, , 2008Raichaudhuri et al, 2009). In plants, both folate biosynthetic and folatedependent enzymes are distributed among three cellular compartments: plastids, mitochondria, and the cytosol (Appling, 1991;Rébeillé et al, 2006;Loizeau et al, 2008;Fig.…”
mentioning
confidence: 99%
“…1). Polyglutamylation is also essential for the retention of folates within a given cellular compartment, since organellar folate transporters are more specific to monoglutamylated folates (Bedhomme et al, 2005;Klaus et al, 2005;Raichaudhuri et al, 2009). In Arabidopsis, three genes, AtDFB, AtDFC, and AtDFD, have been reported to encode the plastidial, mitochondrial, and cytoplasmic FPGS isoforms, respectively (Ravanel et al, 2001; Fig.…”
mentioning
confidence: 99%
“…In fact, all plant PGP transporters characterized so far appear to be involved in cellular and long-distance auxin transport (Terasaka et cerevisiae. In addition, several are able to transport other amphipatic organic anions, such as linear tetrapyrroles derived from chlorophyll catabolism and folates (Lu et al, 1998;Raichaudhuri et al, 2009). Functional analysis of four Arabidopsis MRP isogenes (AtMRP1, 2, 11 and 12) has shown that their contribution to detoxification is marginal, as the corresponding loss-of-function mutants showed no drastic changes in sensitivity towards different herbicides.…”
Section: Abc Transportersmentioning
confidence: 99%